PEMBINAAN AKHLAK REMAJABERBASIS MASJID DI MASJID THAYYIBAHDESA TUMPUK TANGAH KECAMATAN TALAWI - Syafril, Syafril (State Institute for Islamic Studies Batusangkar, 2019)
This study aims to find and analyze mosque-based adolescent moral coaching, to find out and analyze the obstacles faced by various parties in mosquebased adolescent moral development, and to find out and analyze solutions that can be done in mosque-based adolescent moral development in Thayyibah Mosque, Talawi District. This research is descriptive qualitative. Informants in the study were mosque administrators, youth mosque leaders, and Stacked Village Heads. Data collection tools are researchers as key instruments and supporting instruments are interview guidelines, observation guidelines, field notes, and recording devices. Data collection techniques are participatory observation, indepth interviews and documentation studies. Data analysis techniques use domain analysis, carry out taxonomy analysis, conduct compential analysis and conduct theme analysis. The results showed that mosque-based adolescent moral coaching at Thayyibah Mosque in Stacked Village is through congregational prayer, majelis ta'lim, social activities, commemoration of Islamic holidays (PHBI), and tadarrus of the Qur'an. While the solution taken in this mosquebased youth moral development is always to hold discussions with the government, religious leaders, traditional leaders, and with the parents of the teenagers themselves, to convey information in the presence of recitation wirid, to form activities that touch directly on youth activities, and provide examples of admirable behavior to teenagers